THE INFLUENCE OF USING THINK PAIR SHARE AND PAIRS CHECK TEHNIQUE TOWARD STUDENTS’ WRITING ABILITY IN RECOUNT TEXT AT THE STUDENTS OF SMP N 2 PEKALONGAN ACADEMIC YEAR 2013/2014 - Lia Aris Tantya; Syaifudin Latif Darmawan (Premise: Journal of English Education and Applied Linguistics, 2014)
Abstract: The objective of this research are to find out whether, the result of students’ score by using Think Pair Share Technique maximal, the result of students’ score by using Pairs Check Technique maximal and students’ score of Writing Ability in Recount Text, how far the result of Influence of  Using Think Pair Share and Pairs Check Tehnique toward Students Writing Ability in Recount Text. This research is Quantitative research. Research design that will be used in this research is true experimental design. The population of this research is the students’ of SMP N 2 Pekalongan in 2013/2014 that consist of 603 students. The sample is 60 students. As the sample, 30 as experimental class and 30 as  control class. In taking sample, the researcher used the cluster random sampling. The data collecting tehniques the researcher used are try-out, pre-test, treatment and post-test. The data analyzing tehniques, the researcher used normality test, homogenity test and hypothesis test. The differences of both the tehnique are TPS Tehnique can make students enjoy and fun in learning process because it is adopted by Share and can make students be active in learning. Based on the data analysis, the researcher uses t-test formula. The researcher got the result of tobserved = 2.78 and ttable is 2.00. it means that tobserved > ttable. And the criterion of ttest is Ha accepted if tobserved > ttable . So, there is differences between using TPS and Pairs Check tehnique toward students’ writing ability in recount text at the students of SMP N 2 Pekalongan in academic year 2013/2014.